2005
DOI: 10.1074/jbc.m414535200
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid-modified Phosphoinositide-specific Phospholipase C (TcPI-PLC) Is Involved in Differentiation of Trypomastigotes to Amastigotes of Trypanosoma cruzi

Abstract: The phosphoinositide-specific phospholipase C (PI-PLC) is an important component of the inositol phosphate/diacylglycerol signaling pathway. A newly discovered Trypanosoma cruzi PI-PLC (TcPI-PLC) is lipid modified in its N terminus, targeted to its plasma membrane, and believed to play a role in differentiation of the parasite because its expression increases during the differentiation of trypomastigote to amastigote stages. To determine whether TcPI-PLC is involved in this differentiation step, antisense inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
(60 reference statements)
4
40
0
Order By: Relevance
“…A number of proteins in kinetoplastids had been previously reported to undergo thioacylation, including SMP-1 (35) and hydrophilic acylated surface proteins (5) of Leishmania major, protein phosphatases with EF hand domains of L. major and T. brucei (24), phosphoinositide-specific phospholipase C (PLC) (12,26) and FCaBP of T. cruzi (13), and glycophosphatidylinositol-PLC (28), calflagins (8,10), and CAP5.5 (15) of T. brucei. Our previous finding that calflagin palmitoylation was mediated by a single DHHC-CRD protein, TbPAT7, established the conservation in T. brucei of PAT activity by DHHC-CRD proteins (10).…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteins in kinetoplastids had been previously reported to undergo thioacylation, including SMP-1 (35) and hydrophilic acylated surface proteins (5) of Leishmania major, protein phosphatases with EF hand domains of L. major and T. brucei (24), phosphoinositide-specific phospholipase C (PLC) (12,26) and FCaBP of T. cruzi (13), and glycophosphatidylinositol-PLC (28), calflagins (8,10), and CAP5.5 (15) of T. brucei. Our previous finding that calflagin palmitoylation was mediated by a single DHHC-CRD protein, TbPAT7, established the conservation in T. brucei of PAT activity by DHHC-CRD proteins (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, the full-length protein localizes to intracellular membranes by virtue of additional protein-protein interactions. Similarly, the T. brucei protein CAP5.5 (Hertz-Fowler et al, 2001) and the T. cruzi protein TcPI-PLC (Furuya et al, 2000;Okura et al, 2005) are dually acylated, yet localize to the pellicular membrane. For CAP5.5, this is believed to be mediated by a biochemical association with subpellicular microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1% radioactivity was found in these trypomastigotes. Control and infected cells were incubated for 6,12,18,21,24,30,48, and 72 h. Three hours before each extraction, LiCl (15 mM) was added to the culture medium to inhibit inositol phosphatase activities. Inositol phosphates were analyzed as described before (15) at the times indicated.…”
Section: Methodsmentioning
confidence: 99%
“…However, the T. cruzi enzyme possesses N myristoylation and palmitoylation consensus sequences that have not been described in any other PI-PLC and has been shown to be N myristoylated and palmitoylated in vivo (6). It has been shown that this lipid modification is important for its plasma membrane localization and for differentiation of trypomastigotes into amastigotes (18). The enzyme has been shown recently to localize to the outer surface of the plasma membrane of amastigotes (12).…”
mentioning
confidence: 99%